APPIRO: IoT and GPS-Based Brake Failure Detection and Early Warning Device for Freight Vehicles - Fadhli Yusuf As Shiddiq; Sutan Muhammad Fachri; Bagus Andrianto (Pelopor Publikasi Akademika, 2026)
Traffic accidents due to brake failures in freight vehicles in Indonesia account for around 90 percent of the total traffic accidents. This condition prompted researchers to create APPIRO (Brake Blong Detection and Early Warning Tool) based on IoT and GPS, which functions to provide early warning of potential braking system failures in real-time to reduce the number of accidents caused by freight transportation that experiences brake failure. This study aims to design, calibrate, and evaluate APPIRO tools in detecting over-temperature in brake systems and loads in freight transport vehicles. R&D (Research and Development) research methods include hardware design, application manufacturing, calibration of Thermocouple Type K, Loadcell Type S sensors, and limited scale trials. APPIRO's main components consist of thermocouple type K temperature sensor, S type loadcell, ESP32 microcontroller, GPS Tracker NEO6MV2 module, HX711 module, MAX6675 module, dual channel relay, 16x2 LCD, IoT-based Kodular application that displays real-time temperature, load, vehicle location data and early warning notifications. The calibration results at the Center for Standardization and Industrial Services showed a relative error of the thermocouple sensor of –1.11% and the loadcell of 1.48%, which is still within acceptable accuracy limits. Limited trials showed that in pick-up vehicles with a load of 2476.9 kgf, the brake oil temperature increased to 212.4°C so that the system gave a